EFFECT OF COMPENSATION ON EMPLOYEE PERFORMANCE AND INTER-WORK CONFLICT AS MODERATION VARIABLES (Case Study at the Public Works and Public Housing Agency of Bulungan Regency) - Tuti Suriyani; Ana Srie Kaningsih; Elizabeth Novi Kusumaningrum; Tou Qinglin (STKIP Singkawang, 2022)
The purpose of this study is to prove and analyze the effect of compensation on employee performance, and to prove and analyze the effect of inter-job conflict as a moderating variable between compensation on the performance of the Public Works and Public Housing Department of Bulungan Regency. The location of this research is the Public Works and Public Housing Agency of Bulungan Regency. The time of the study began in May – July 2021. The research sample used in this study was 47 respondents. The data analysis technique used is a moderation regression analysis approach. The results showed that the compensation variable had a significant effect on the performance of the employees of the Public Works and Public Housing Office of Bulungan Regency. Conflict between jobs is a moderating variable between compensation and employee performance. This shows that the relationship between these two variables can be intervened with inter-job conflict variables, where the results of this intervention will have a strong or weak impact on the relationship between compensation variables and employee performance.